1995
DOI: 10.1128/cmr.8.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pyrogenic exotoxins as superantigens

Abstract: The recent discovery of the mode of interaction between a group of microbial proteins known as superantigens and the immune system has opened a wide area of investigation into the possible role of these molecules in human diseases. Superantigens produced by certain viruses and bacteria, including Mycoplasma species, are either secreted or membrane-bound proteins. A unique feature of these proteins is that they can interact simultaneously with distinct receptors on different types of cells, resulting in enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(110 citation statements)
references
References 293 publications
1
102
0
7
Order By: Relevance
“…The frequencies of inflammatory cytokineproducing cells found in the circulation of patients with severe invasive GAS infections, which reached above 20% for a single cytokine in some STSS patients, corresponded well to frequencies expected for a superantigen response (5-40%). This provides further support for the proposed central role of streptococcal superantigens in the pathogenesis of severe invasive GAS disease [4][5][6][7]. Furthermore, these findings are in agreement with a recent study by Arad et al [31], which showed that inhibition of superantigen induced cytokine expression by peptide antagonist protected mice against toxic shock.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The frequencies of inflammatory cytokineproducing cells found in the circulation of patients with severe invasive GAS infections, which reached above 20% for a single cytokine in some STSS patients, corresponded well to frequencies expected for a superantigen response (5-40%). This provides further support for the proposed central role of streptococcal superantigens in the pathogenesis of severe invasive GAS disease [4][5][6][7]. Furthermore, these findings are in agreement with a recent study by Arad et al [31], which showed that inhibition of superantigen induced cytokine expression by peptide antagonist protected mice against toxic shock.…”
Section: Discussionsupporting
confidence: 82%
“…Superantigens produced by GAS are believed to be central mediators of the systemic effects seen in severe invasive GAS disease (reviewed in [4][5][6][7]). GAS express several different antigens and superantigens capable of eliciting cytokine responses and activating a large proportion of immune cells (reviewed in [4,5,7]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Während die SE Superantigencharakter aufweisen, also in der Lage sind, T-Zellen unspezifi sch zu aktivieren (Polyklonale T-Zellen-Stimulation mit Zytokin-und Mediatorenausschüt-tung sowie Gerinnungs-, Komplement-und Plättchenaktivie-rung, wodurch die Endothelzellen geschädigt, der periphere Gefäßwandwiderstand gemindert und Kapillarleckagen mit septischem Schock und Immunsuppression initiiert werden) (Marrack und Kappler, 1990;Fleischer, 1995;Kotb, 1995;Müller-Alouf et al, 2001;Baker und Archarya, 2004), haben trotz ihres Namens nicht alle SE auch Enterotoxincharakter. Um dies in der Nomenklatur der Toxine deutlich zu machen und um Mißverständnissen vorzubeugen, schlug das International Nomenclature Committee for Staphylococcal Superantigens (INCSS) folgende Regeln für die Bezeichnung neu beschriebener bzw.…”
Section: Se-typunclassified
“…Der Nachweis von Staphylococcus aureus oder des Toxins (Toxic-shock-Syndrom-Toxin-1) gelingt jedoch nicht in allen Fällen. Die Wirkungsweise des Toxic-shock-Syndrom-Toxin-1 ist gut erforscht [4,8] …”
Section: Kasuistikunclassified